2020
DOI: 10.28940/terra.v38i2.645
|View full text |Cite
|
Sign up to set email alerts
|

Rediseño óptimo de la red presurizada de la sección 01, del distrito de riego 001 Pabellón de Arteaga, Aguascalientes

Abstract: El recurso agua es cada día más limitado, siendo la agricultura el sector que mayor demanda tiene, por lo que es necesario contar con infraestructura de riego capaz de optimizar y suministrar el agua que recibe la planta. El presente trabajo tuvo como objetivo rediseñar y optimizar la sección 01 del distrito de riego 001 (DR 001) Pabellón de Arteaga, Aguascalientes para que la red pueda satisfacer los requerimientos de agua de los cultivos con el sistema de suministro del riego a la demanda. Se aplicó la prime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
(2 reference statements)
0
0
0
Order By: Relevance
“…Several studies have reported the use of classical optimization techniques in choosing the most feasible and least costly sizing, such as linear programming (Galván-Cano & Exebio-García, 2020;Soler et al, 2016). This method presents an optimal solution that depends entirely on the input parameters, which are fixed, but resource availability constraints present some inaccuracies under actual situations (Zhang & Guo, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported the use of classical optimization techniques in choosing the most feasible and least costly sizing, such as linear programming (Galván-Cano & Exebio-García, 2020;Soler et al, 2016). This method presents an optimal solution that depends entirely on the input parameters, which are fixed, but resource availability constraints present some inaccuracies under actual situations (Zhang & Guo, 2018a).…”
Section: Introductionmentioning
confidence: 99%